Bi-layer Channel AZO/ZnO Thin Film Transistors Fabricated by Atomic Layer Deposition Technique - Li, Huijin (Nanoscale Res Lett, 2017)
This letter demonstrates bi-layer channel Al-doped ZnO/ZnO thin film transistors (AZO/ZnO TFTs) via atomic layer deposition process at a relatively low temperature. The effects of annealing in oxygen atmosphere at different temperatures have also been investigated. The ALD bi-layer channel AZO/ZnO TFTs annealed in dry O(2) at 300 °C exhibit a low leakage current of 2.5 × 10(−13)A, I (on)/I (off) ratio of 1.4 × 10(7), subthreshold swing (SS) of 0.23 V/decade, and high transmittance. The enhanced performance obtained from the bi-layer channel AZO/ZnO TFT devices is explained by the inserted AZO front channel layer playing the role of the mobility booster.